(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: sub district head as the head of the unit of work in a sub district supervisory functions as the roles to improve effectiveness and efficiency of the work of employees concerning the services that come into contact with the community. The purpose of this research is to know the description of the function of supervision of the sub district head to increase the efficiency and effectiveness of work of employees in the sub district Kawangkoan Minahasa regency This research uses Qualitative Descriptive method where data retrieval in field or object of research data collected by researchers in person with the intention of directly spaciousness. The determination of sample respondents conducted in purposive sampling where writers/researchers specify or choose deliberately against the sample of respondents that add up to 17 people The supervisory function of the sub district head in the improvement of work productivity in the Government apparatus sub district Kawangkoan views efficiency and effectiveness is already well underway. This is apparent in the management control through the Organization, in the implementation of policies, procedures and job duties. Several other factors that have not been fullest including mental attitude is still lacking but if any deficiencies there may be clear in the implementation of the duties and responsibilities of the employees will be the maximum so that it will have an effect on the success of the tasks performed, both in the areas of governance, development, community, and other administrative tasks. Keywords: supervision, efficiency, effectiveness